Lupus miliaris disseminatus faciei: A report with a new dermoscopy finding - Basavapura Madegowda Shashi Kumar; Allaranda Somiiah Savitha (Our Dermatology Online, 2021)
Lupus miliaris disseminatus faciei (LMDF) is a rare inflammatory disorder characterized by asymptomatic papular lesions mainly over the central part of the face, common in young adults and with a spontaneously resolving course. Its exact etiology remains unknown, its treatment is problematic, and there is a lack of controlled studies on LMDF. Histopathology shows dermal epithelioid granulomas with central necrosis and surrounding lymphocytic infiltrate with multinucleate giant cells. Dermoscopic findings published show discrete focal orangish structureless areas located around follicular openings with whitish keratotic plugs. Herein, we report a case of LMDF with dermoscopy showing stellate scar signs and structureless white areas.